Inativação fotodinâmica da bactéria Staphylococcus aureus resistente à meticilina: avaliação de doses fracionadas de luz e fotossensibilizador curcumina - Cappellini, Taina Cruz de Souza (Universidade Federal de São Carlos, 2025)
The emergence of resistant bacteria in the community and hospital environment may be a consequence of the excessive and improper use of antibiotics over time, putting the health of the world population at risk. Due to bacterial resistance, we have sought alternative methods to treat infections caused by microorganisms. Photodynamic inactivation (PDI) has become a focus of study for the treatment of bacterial infections, which is based on a photosensitive substance, light and molecular oxygen. The objective of this study was to evaluate the action of different concentrations of the photosensitizer (PS) curcumin, together with variations in the delivery of the light dose to inactivate the bacterium methicillin-resistant Staphylococcus aureus (MRSA), obtained by clinical isolate. The study of the photodegradation of curcumin at concentrations of 10, 20 and 40 μM, illuminated with 450 nm light, with a dose of 57.6 J/cm², over 24 min, was carried out, accompanied by ultraviolet-visible absorption spectroscopy and molecular fluorescence. In addition, the process of curcumin internalization (10 μM) by MRSA was also monitored by confocal microscopy for 20 min. The IFD assays with MRSA were divided into stages. In the first stage, a conventional IFD was performed with different concentrations (5, 10, and 15 μM) and illuminated at 450 nm at energy doses (5, 10, and 15 J/cm²). In the second stage, after optimizing the result of the conventional IFD, a fractional IFD was performed by fixing the FS concentration at 10 μM and varying the energy doses at intervals of 10 and 30 minutes. Thus, confocal microscopy experiments of MRSA cell predictions were performed after treatment with fractional IFD and at intervals of 30 min. The oxygen concentration analysis experiments were performed by an electrode, monitoring a percentage of O2 in a 10 μM curcumin solution. The results of conventional IFD demonstrated effectiveness in inactivating MRSA bacteria at concentrations of 5, 10, and 15 μM for the energy doses evaluated. However, the most significant reduction was 3.41 and 4.34 logs and 3.51 and 4.95 logs for concentrations of 10 and 15 μM at doses of 10 and 15 J/cm² with conventional IFD, respectively. In fractionated IFD, the most significant result was 5.67 logs of reduction of the microorganism with the energy dose of 10 J/cm² fractionated at 30-minute intervals, when compared to conventional IFD at the continuous dose of 10 J/cm². There was also effectiveness at the energy dose of 15 J/cm² with intervals of 10 and 30 minutes, compared to the conventional one, with reductions of 4.96 and 5.45 logs, respectively. The formation of reactive oxygen species (ROS) in the curcumin solution was analyzed using the dihydroethidium (DHE) probe, after continuous and fractional irradiation at intervals of 10 and 30 min. It was concluded that the fractionation of energy doses demonstrated the potential to achieve better results compared to the application of continuous doses, showing a more effective approach for the inactivation of bacteria in microbiological studies. However, further studies are needed to determine the ideal parameters that improve the efficiency of the photodynamic process.
Photodynamic inactivation of methicillin-resistant Staphylococcus aureus bacteria: evaluation of fractionated doses of light and photosensitizer curcumin
Keywords: Inativação fotodinâmica; Fotodegradação; Fracionada; Curcumina; Bactérias resistentes; Antibióticos; Photodynamic inactivation; Photodegradation; Fractional; Curcumin; Resistant bacteria; Antibiotics; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; CIENCIAS EXATAS E DA TERRA::FISICA